Data: Gene expression of Mowat-Wilson syndrome patient derived GABAergic interneurons - Klar, Joakim; Dahl, Niklas; Schuster, Jens (Uppsala University, 2022)
IPSC lines established from fibroblasts of both sibling (MW1=26, MW2=27) and two healthy donors (Ctl2=K02 and Ctl8=K08).

Neurocortical differentiation of iPSCs (samples IPS) was carried out as described using Dual-SMAD inhibition that promotes conversion into neural stem cells (NSC) for 10 days (samples INT) followed by directed differentiation into cortical lineages for 65 days (samples D65).

Bulk RNA sequencing reads were aligned to the ENSEMBL human reference genome (Homo_sapiens.GRCh37.75) and gene counts were generated using the STAR read aligner. The count data is not normalized and can be used with DESEq2.

Expression data was generated for all three time points IPS -> INT (D10) -> D65

File names are:

timepoint_SampleReadsPerGene.out.tab
Keywords: Gene expression (incl. microarray and other genome-wide approaches); Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik